2020
DOI: 10.1002/adfm.201909942
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Memristivity by Varying the Oxygen Content in a Mixed Ionic–Electronic Conductor

Abstract: The rising interest shown for adaptable electronics and brain-inspired neuromorphic hardware increases the need for new device architectures and functional materials to build such devices. The rational design of these memory components also benefits the comprehension and thus the control over the microscopic mechanisms at the origin of memristivity. In oxidebased valence-change memories, the control of the oxygen drift and diffusion kinetics is a key aspect in obtaining the gradual analog-type change in resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In electrochemical metallization memories, cations from an active electrode migrate reversibly in an insulating matrix, reaching the inert electrode and leading to a change in resistance. In valence change memories (VCMs) with electrode/oxide/electrode configuration, where the oxide can be insulating, such as HfO2, [3] TaOx, [4,5] SrTiO3, [6] or semiconducting, [7] such as LaMnO3, [8] or La2NiO4, [9][10][11] the resistance is modified by the drift of oxygen ions (or oxygen vacancies) and the concomitant local valence change of the cationic sublattice. Nonetheless, in many cases electronic and ionic effects interplay to give raise to the memristive response.…”
Section: Introductionmentioning
confidence: 99%
“…In electrochemical metallization memories, cations from an active electrode migrate reversibly in an insulating matrix, reaching the inert electrode and leading to a change in resistance. In valence change memories (VCMs) with electrode/oxide/electrode configuration, where the oxide can be insulating, such as HfO2, [3] TaOx, [4,5] SrTiO3, [6] or semiconducting, [7] such as LaMnO3, [8] or La2NiO4, [9][10][11] the resistance is modified by the drift of oxygen ions (or oxygen vacancies) and the concomitant local valence change of the cationic sublattice. Nonetheless, in many cases electronic and ionic effects interplay to give raise to the memristive response.…”
Section: Introductionmentioning
confidence: 99%
“…Point defects such as oxygen vacancies play an important role in memristive devices. [1][2][3][4] Particularly in devices comprising thin films, these materials operate under high electric fields (on the order of megavolt per centimeter). Recent studies have shown DOI: 10.1002/advs.202104476 that polarization of point defects under such high electric fields can strongly impact defect formation, [5] transport, [6] and distribution, as well as dielectric response, [7] which are integral to device performance.…”
Section: Introductionmentioning
confidence: 99%
“…This interlayer acts as an oxygen getter or oxygen reservoir and plays a key role in the memristive properties of the given device. [21][22][23] A vertical configuration is commonly used for memristors due to its reduced dimensions, compactness, and easiness for ReRAM devices fabrication, as well as compatibility for integration in cross-bar array architectures. [24] Nevertheless, given the small series resistance of the memristive layer, in particular for semiconducting oxides, which results from low film thickness (between a few nm to a few tens of nm), to avoid the device breakdown, the electrical current density should be carefully controlled by the current compliance.…”
Section: Introductionmentioning
confidence: 99%